2007
DOI: 10.1634/theoncologist.12-6-622
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between RRM1 Haplotype and Gemcitabine-Induced Neutropenia in Breast Cancer Patients

Abstract: Purpose. We examined the pattern of single-nucleotide polymorphisms (SNPs) of gemcitabine metabolism-related and target genes in breast cancer patients and evaluated their association with drug response or toxicity.Patients and Methods. SNPs in deoxycytidine kinase (dCK), deoxycytidine monophosphate deaminase (DCTD), and ribonucleotide reductase M1 polypeptide (RRM1) were analyzed with genomic DNA of 10 breast cancer cell lines, 74 peripheral blood mononuclear cell (PBMC) samples from advanced breast cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…It should be noted that the validation material used in this study was not completely independent of the screening because the remaining non-extreme patients were used for the validation in addition to an independent patient cohort. Several studies have previously associated toxicity and response with variants of candidate genes involved in metabolism and transport of gemcitabine such as CDA, dCK, SLC28A1, SLC28A3 as well as target molecules RRM1, RRM2 and RRM2b (19)(20)(21)(22)(23)(24). In a recent metaanalysis, the genetic variant A79C in the CDA gene was associated with severe anemia, but without being able to show an effect related to neutropenia, thrombocytopenia, or response (25).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the validation material used in this study was not completely independent of the screening because the remaining non-extreme patients were used for the validation in addition to an independent patient cohort. Several studies have previously associated toxicity and response with variants of candidate genes involved in metabolism and transport of gemcitabine such as CDA, dCK, SLC28A1, SLC28A3 as well as target molecules RRM1, RRM2 and RRM2b (19)(20)(21)(22)(23)(24). In a recent metaanalysis, the genetic variant A79C in the CDA gene was associated with severe anemia, but without being able to show an effect related to neutropenia, thrombocytopenia, or response (25).…”
Section: Discussionmentioning
confidence: 99%
“…19,27,29 No significant associations were detected for both RRM1 G2464A and A2455G polymorphisms and RRM1 gene expression. These results are in agreement with a previous study showing no significant association between mRNA levels of wild-type and polymorphic types in RRM1 G2464A alone (P ¼ 0.301), or a combination of several types of RRM1, including RRM1 A2455G, in 62 human cancer cell lines were used, including six lung cancer cell lines.…”
Section: Expression Of Drug-related Genes In Nsclcmentioning
confidence: 94%
“…28 In the same study, the RRM1 G2464A polymorphism demonstrated an association with gemcitabine sensitivity, 30 while together with the A2455G polymorphism was associated with neutropenia after gemcitabine treatment in breast cancer patients. 29 Therefore, further functional studies evaluating coexpressing genes, as well as prospective clinical trial for its application as a predictive biomarker are needed.…”
Section: Expression Of Drug-related Genes In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RRM1 is the molecular target of gemcitabine, and its mRNA expression levels are related to the efficacy of gemcitabine therapy 7, 8. The RRM1 polymorphism – 37 C<A and haplotype – was shown to be associated with susceptibility to gemcitabine in cancer patients including lung cancer 9, 10. However, the relationship between the ribonucleotide reductase M1 ( RRM1 ) gene and susceptibility to lung cancer has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%